ANALISIS PENGARUH IKLAN DI SOSIAL MEDIA INSTAGRAM DAN DISKON HARGA TERHADAP PERILAKU KONSUMTIF PELAKU COSPLAY DI KOTA MEDAN - Rusdiana Simamora; Hendy; Anastacia Jocelym (Halu Oleo University, 2024)
In the cosplay entertainment, consumers will take advantage of the various offers given by businessmen to support their cosplay activities. Of the many promotional strategies available, some of the ways that businessmen do is to display ads on social media Instagram and make discount prices on products. The research is aimed at finding out how much impact ads factors on social media Instagram and price discount factors have on the consumptive behaviour of the cosplayers. The type of research used is quantitative research with the collection of primary data through questionnaires of 96 cosplayers in Medan. Data processing utilizes IBM SPSS Statistics 25 program, with multiple linear regression analysis. The results of the test hypothesis showed that the ads on Instagram has a positive and significant effect on the consumptive behavior of cosplayers, with a tvalue (2,015) > ttable (1,985) at a significance rate of 0,047 < 0,005. The price discount also has a positively and significant effect on the consumptive behaviour of cosplayers, with the tvalue (3,461) > ttable (1,985), at a significance rate of 0,001 < 0,05. Simultaneously, the ads on Instagram and the price discount have a positive and significant effect on consumptive behaviors of cosplayers, by the Fvalue (15,96) > Ftable (3,09) at a significant rate of 0,000 < 0,05.